Outstanding characteristics of psychopaths integrated into everyday life. Literature review - Silva , Luciano Barreto; Duarte, Marvin Gonçalves; Cunha , Rodolfo Scavuzzi Carneiro; Castro , Marcos José Araújo de; Amaral , Lucas de Jesus Santana do; Rêgo, Ana Carolina Bastos do; Brandão, Rita de Cássia Vieira de Vasconcelos Cavalcanti (Seven Editora, 2023)
Objective: To describe the main characteristics of psychopaths including their sexual habits in their ritual of charming, dominating, and abandoning their victims, as well as explain the chaos and devastation they cause in them. Finally, suggest treatment approaches for victims in the damage recovery process. Methodology: Interviews were conducted with victims of psychopaths who lived with them for more than a decade. Information concerning sexual habits was carefully categorized and explained. As support, online searches for the construction of this article were carried out in the databases of Google Scholar, PUBMED Central, Web of Science, BVS / BIREME, Science Direct, Scielo, The Cochrane Library, and also by PROSPERO. The identities of victims and psychopaths were kept confidential. Results: The sexual habits of psychopaths include 3 stages: initial love bombing, humiliation, and domination of the victim, and finally abandonment after sexual, emotional, and financial exploitation. The main consequences in the lives of partners include chaos, sleep and eating disorders, anger, despair, and depression, and in some cases lead to death. Conclusions: psychopathy has no treatment, and due to the devastation, it causes in people due to the feeling of betrayal, exploitation, and lack of love, it causes victims to have all aspects of their lives destroyed. The only way to fight it is through knowing the psychopath’s mind and what they can do. DOI:https://doi.org/10.56238/devopinterscie-260